The role and targeting potential analysis of angiogenesis-related target THY1 in DSS-induced acute colitis in mice - Pengliang Zhang; Xianmin Liu; Shuang Chen; Yingjian Zhang (PLoS ONE, 2026)
Background Immune-driven inflammatory angiogenesis plays a crucial role in the pathogenesis of inflammatory bowel disease (IBD). However, the mechanism of chronic inflammation mediated by angiogenesis still remains unclear. This study aimed to investigate the crucial role and specific mechanism of the angiogenesis-related target THY1 in the development of acute colitis induced by dextran sulfate sodium (DSS) in mice. Methods Lentivirus-based systems were utilized to achieve both knockdown and overexpression of THY1 to explore the functional roles of THY1 in IBD development based on DSS-induced colitis mice model and co-culture system of intestinal epithelial cells and macrophages. Results THY1 significantly promotes DSS-induced colitis in the experimental mouse model. Silencing of the THY1 significantly reversed the inflammatory response, oxidative stress level, and angiogenic activity in DSS-induced colitis, whereas overexpression of THY1 further exacerbating the reactions related to inflammation, oxidative stress, and angiogenesis. Mechanism research showed that THY1 promotes the pathological process of DSS-induced colitis through inhibiting M2 macrophage polarization. In addition, THY1 promotes apoptosis through the Bcl-2/Bax/Cleaved caspase-3 pathway and promotes angiogenesis via upregulation of HIF-1α and VEGF expression in DSS-induced colitis. Conclusions THY1 promotes the occurrence and development of acute colitis induced by DSS in mice by regulating macrophage polarization, intestinal epithelial cell apoptosis, and inflammatory angiogenesis, providing a new perspective for the study of the pathogenesis of IBD. Furthermore, THY1 is expected to become a potential target molecule for the treatment of IBD.